Kepentingan Nasional Indonesia dan Diplomasi ala Indonesia dalam Penyelesaian Konflik Rohingya - Glen Matthew (Jurnal Hubungan Internasional, 2020)
ABSTRAKRohingya conflict in Myanmar has been a crucial issue in the midst of global society. Having been rolling since the British colonial era in Myanmar, concrete actions are needed in resolving conflicts, which involving Rohingya Muslims and Buddhist Rakhine. This conflict has spread to sectarian conflicts and therefore must be resolved immediately. This article is written to see national interest of Indonesia and Indonesian way of diplomacy as a country with largest Muslim population in the world, also as a fellow ASEAN countries, in ending the Rohingya conflict. Researcher will observe Indonesia’s national interest in this issue using the paradigm of realism, one of the theories in the study of International Relations. Realist thought is based on the search for power and domination. The research will use qualitative methods conducted by doing a literature study. The results of research from various source, show that in achieving national interests, Indonesia must use Indonesian style diplomacy summarized in a free and active foreign policy.Keywords: Conflict, Rohingya, Indonesia, Myanmar, National Interest, Diplomacy, RealismKonflik Rohingya di Myanmar, sudah sekian lama menjadi isu yang krusial di tengah-tengah masyarakat global. Telah bergulir sejak era penjajahan Inggris di Myanmar, diperlukan langkah-langkah konkrit dalam penyelesaian konflik yang melibatkan kaum Muslim Rohingya dan Rakhine yang beragama Buddha. Konflik ini telah merambah menuju konflik sektarian dan oleh karena itu harus segera diselesaikan. Artikel ini bertujuan untuk melihat kepentingan nasional Indonesia dan cara Indonesia berdiplomasi sebagai negara dengan jumlah penduduk Muslim terbesar di dunia dan juga sebagai sesama negara ASEAN, dalam penyelesaian konflik Rohingnya. Peneliti akan mengamati kepentingan nasional Indonesia dalam isu ini dengan menggunakan paradigma realisme, salah satu teori dalam studi Hubungan Internasional. Pemikiran kaum realis sendiri berlandaskan pada pencarian kekuasaan dan dominasi. Penelitian akan menggunakan metode kualitatif yang dilakukan dengan cara melakukan studi literatur. Hasil penelitian dari berbagai sumber, menunjukkan bahwa di dalam mencapai kepentingan nasional, Indonesia harus menggunakan diplomasi ala Indonesia yang terangkum dalam kebijakan politik luar negeri bebas aktif.